Learning by enacting: The role of embodiment in chemistry education. (June 2018) - Stull, Andrew T.; Gainer, Morgan J.; Hegarty, Mary
Abstract: Can students learn from viewing an instructor's model-supported demonstrations alone or do they benefit from physically enacting the demonstrated concepts? This study investigated the value of enactment when learning chemistry using 3D molecular models in video and classroom lectures. We hypothesized that students who used models to enact demonstrated concepts would learn more than those who only watched a model-supported demonstration. Students watched a video lecture in a small classroom in Study 1 and a live lecture in a large lecture hall in Study 2. In both studies, one group watched and enacted the instructor's model-supported demonstration and the second group watched without enacting. In both contexts, students learned more if they enacted the demonstration than if they just watched the demonstration. Specifically, those who used models to enact an instructor's demonstrations performed better on problems that required drawn answers. Learning from enacted demonstrations was resilient over a delay of five days between instruction and testing and transferred to performance on classroom assessments that differed from the demonstrated tasks. We conclude that enactment with hand-held models promoted learning by off-loading the demand of imaging concepts and processes in the mind on to external objects and actions in the world, and that meaningful learning was promoted by lowering cognitive load while enhancing generative processing. Highlights: Students learned more when they enacted a demonstration with 3D models than when they only watched the demonstration. Enacting a demonstration was beneficial for learning from a video lecture and from a live lecture in a large hall. The benefits of enacting were specific to learning outcomes that required students to draw spatial diagrams. Learning by enacting demonstrations was resilient over a delay of five days between instruction and testing. Learning by enacting contributed to far transfer with students performing better on a variety of exam problems.